Gas-Bearing Characteristics of the Longmaxi Formation Shale in the Changning Area, Southern Sichuan Basin, SW China - Lu, Chang; Chen, Lei; Jing, Cui; Tan, Xiucheng; Nie, Zhou; Chen, Xin; Heng, De (Frontiers in Earth Science, 2022)
The Changning Area, located in the south of the Sichuan Basin, has obtained commercial shale gas from the Silurian Longmaxi Formation which is characterized by rich in organic matter, large in hydrocarbon generation and high gas content. A series of studies have been carried out on the shale of Wufeng Formation-Longmaxi Formation in Changning area, including mineral petrological characteristics, shale reservoir characteristics, enrichment and accumulation characteristics, etc. Although there are studies on the gas-bearing characteristics of the Wufeng Formation-Longmaxi Formation shale in Changning area, the research is not systematic. In this work, based on isothermal adsorption experiments, field desorption experiments and well log interpretation, the gas-bearing characteristics of the Longmaxi Formation shale in the Changning area was studied in detail. The results showed that the average of saturated-adsorbed methane gas volume of the Longmaxi Formation is 1 m3/t, which demonstrated that the Longmaxi shale reservoirs had strong adsorption capacity. The total gas content of the section Long11-1, Long11-2, Long11-3 and Long11-4 are greater than 2m3/t, which were prolific shale gas layers. The Long12 sub-member has the lowest total gas content, ranging from 0.34 m3/t to 3.84 m3/t, with an average of 1.59m3/t. The free gas content of the Longmaxi Formation in Changning area was slightly smaller than the adsorbed gas content and it shows increasing trend from bottom to top, while the adsorbed gas content shows opposite trend. With the top of Long11-3 as the circumscription, the adsorbed gas accounts for the main part of shale gas in the lower part, and the free gas shale gas in the upper part.